2021
DOI: 10.1002/iub.2460
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence: Silent operator and therapeutic target in cancer

Abstract: The process of carcinogenesis and its progression involves an intricate interplay between a number of signaling networks, metabolic pathways and the microenvironment. These include an alteration in the cellular redox metabolism and deregulation of cell cycle checkpoints. Similar to the dichotomy of redox signaling in cancer cell fate and state determination, a diverging effect of an irreversible cell cycle arrest or senescence on carcinogenesis has been demonstrated. In this regard, while overwhelming oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…Cellular senescence is a cell protective mechanism that can be detected by measuring the SA-β-gal activity 52 , 53 . Several lines of evidence have reported that suppression of cellular senescence is associated with the enhanced carcinogenesis 54 , 55 . Interestingly, several cancer cells can undergo senescence after exposure to chemotherapeutic agents 56 - 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is a cell protective mechanism that can be detected by measuring the SA-β-gal activity 52 , 53 . Several lines of evidence have reported that suppression of cellular senescence is associated with the enhanced carcinogenesis 54 , 55 . Interestingly, several cancer cells can undergo senescence after exposure to chemotherapeutic agents 56 - 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence can play an essential role in immune surveillance to ensure that senescent cancer cells are eliminated ( Prasanna et al, 2021 ). Nowadays, cellular senescence is emerging as a potentially novel anticancer strategy ( Ramu et al, 2021 ). It could help guide effective anticancer therapy strategies by exploring the cellular senescence patterns of GC.…”
Section: Discussionmentioning
confidence: 99%
“…37 In recent years, cellular senescence is gaining recognition as a promising and innovative approach in the field of anticancer strategies. 38 The nomogram had good performance in predicting survival outcomes of GBM patients. The top 30 potential anti-cancer small molecular compounds with higher drug sensitivity scores for high-or low-risk groups were identified, which might be effective to treat GBM patients.…”
Section: Discussionmentioning
confidence: 94%
“…Cellular senescence is essential in immune surveillance, ensuring the elimination of senescent cancer cells 37 . In recent years, cellular senescence is gaining recognition as a promising and innovative approach in the field of anticancer strategies 38 . It has the potential to guide the development of effective anticancer therapies by examining the cellular senescence patterns in GBM.…”
Section: Discussionmentioning
confidence: 99%